2006
DOI: 10.1080/j.1440-1614.2006.01741.x
|View full text |Cite
|
Sign up to set email alerts
|

Stigma about Depression and its Impact on Help-Seeking Intentions

Abstract: Self- and perceived-stigmatizing responses to help-seeking for depression are prevalent in the community and are associated with reluctance to seek professional help. Interventions should focus on minimizing expectations of negative responses from others and negative self-responses to help-seeking, and should target younger people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
396
3
13

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 637 publications
(435 citation statements)
references
References 21 publications
23
396
3
13
Order By: Relevance
“…These results provide preliminary evidence that the stigmatization of patients with AN can lead to delayed treatment initiation. Similar effects were found in studies on stigmatization toward patients with depression [22,23]. The average delay between disease onset and the first consultation with a doctor was shorter than that in previous studies [26,27,28], possibly because participants in the present study were minors at that time and their parents could persuade them to visit a doctor.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results provide preliminary evidence that the stigmatization of patients with AN can lead to delayed treatment initiation. Similar effects were found in studies on stigmatization toward patients with depression [22,23]. The average delay between disease onset and the first consultation with a doctor was shorter than that in previous studies [26,27,28], possibly because participants in the present study were minors at that time and their parents could persuade them to visit a doctor.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, the severity of AN is often underestimated by laypeople [21]. Consequently, as shown by research conducted with patients with depressive symptoms, stigmatization poses a major obstacle to seeking and attending therapy and treatment [14,22,23]. Thus far, previous studies primarily addressed aspects of stigmatization in patients with AN from the point of view of unaffected people.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the Planned Behavior Theory (Ajzen, 1985(Ajzen, , 1991 behavioral intentions are the best predictors of the behavior itself. Although other variables may influence the relationship between help-seeking intentions and behaviors (Barney et al 2006;Schomerus and Angermeyer, 2008), help-seeking intentions seem to elucidate us about the women's help-seeking behaviors in case of an effective need for help (i.e., presenting high levels of perinatal distress). Moreover, we were also interested in examining if women's help-seeking intentions may be different when an effective need of help is present (i.e., presence of high levels of perinatal distress) (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…This is of particular concern as it has been demonstrated that stigmatizing attitudes in this group can lead to diagnostic overshadowing [11] and consequent worsening of physical health care for those with mental health problems [12,13]. Perceived stigma of health care professionals among individuals with mental illness may also reduce willingness to seek help by those who need it [14]. It has been therefore suggested that stigma may partly explain decreased average life expectancy among people with mental health problems [15,16].…”
Section: Introductionmentioning
confidence: 99%